2019
DOI: 10.1177/2381468319866828
|View full text |Cite
|
Sign up to set email alerts
|

Directly Acting Oral Anticoagulants for the Prevention of Stroke in Atrial Fibrillation in England and Wales: Cost-Effectiveness Model and Value of Information Analysis

Abstract: Objectives. Determine the optimal, licensed, first-line anticoagulant for prevention of ischemic stroke in patients with non-valvular atrial fibrillation (AF) in England and Wales from the UK National Health Service (NHS) perspective and estimate value to decision making of further research. Methods. We developed a cost-effectiveness model to compare warfarin (international normalized ratio target range 2–3) with directly acting (or non–vitamin K antagonist) oral anticoagulants (DOACs) apixaban 5 mg, dabigatra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…The comparison of DOACs vs. warfarin in AF has been discussed frequently. Owing to their impressive efficacy and convincing safety profiles reported by RCTs, the economic viability of DOACs has been demonstrated in the US ( 9 , 28 ), European countries ( 10 , 11 ), and in some Asian countries ( 17 , 38 , 39 ). Despite their much higher costs, DOACs are generally more cost-effective than warfarin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of DOACs vs. warfarin in AF has been discussed frequently. Owing to their impressive efficacy and convincing safety profiles reported by RCTs, the economic viability of DOACs has been demonstrated in the US ( 9 , 28 ), European countries ( 10 , 11 ), and in some Asian countries ( 17 , 38 , 39 ). Despite their much higher costs, DOACs are generally more cost-effective than warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their efficacy profiles, which have been recently reported by several large, randomized controlled trials (RCTs), direct oral anticoagulants (DOACs), such as dabigatran, rivaroxaban, apixaban, and edoxaban, are viable alternatives for VKAs and have been established as cornerstones in AF management for the prevention of stroke (7,8). Based on the results of a meta-analysis of RCTs, DOACs have been reported to be more cost-effective than VKAs (9)(10)(11). However, since no RCT was designed to focus on the elderly population specifically, there is little clarity regarding the health and economic benefits of DOACs in the said population (12).…”
Section: Introductionmentioning
confidence: 99%
“…11 A recent systematic review of all RCT data found that all DOACs had a higher expected net benefit than warfarin, at a willingness to pay threshold of £20 000 per quality adjusted life year. 29 This apparent discrepancy may reflect a blunting of DOAC effectiveness in real-world practice, as well as the study's inability to capture the cost to patients and impact on quality of life. Indeed, evidence indicates that patients receiving DOACs report better quality of life scores and lower levels of depression, compared with patients on warfarin.…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
“…Firstly it may require a very large number of samples to characterise the posterior distribution, for example if correlations between parameters impede mixing of the sampler. In addition to needing a large number of samples, it can also be computationally expensive to generate each sample from the posterior, as for the NMA used in the directly acting oral anticoagulants (DOACs) for prevention of stroke in atrial fibrillation Markov model [15, 16, 17, 18]. This can make nested Monte Carlo, or the generation of a sufficient number of samples to determine the regression function for GAM or GP methods, impractical.…”
Section: Introductionmentioning
confidence: 99%
“…Section 4 presents an application to an artificial, but realistic, decision tree depression model with MCMC input parameters. Section 5 presents an application to the published and highly complex DOACs for prevention of stroke in atrial fibrillation Markov model [16, 17, 18]. Further discussions and conclusions are provided in Section 6.…”
Section: Introductionmentioning
confidence: 99%